(untitled) (Research, Society and Development, 2022)
This bibliographic article aims to work on Vygotsky’s theoretical assumptions and his understanding of the expansion of human learning. In order to explain Vygotsky’s line of thought, topics such as life and work, the historical context in which he lived and main ideas about the development of individuals regarding the socio-historical theory and social interactions postulated by him were addressed. The methodology used was the search for a bibliographic structure of articles related to the thinker and his contributions to the educational area as well as the results that aim to mark out that human interactions cooperate in a satisfactory way in the discussions intertwined in the pedagogical processes. Finally, the importance and influence of Vygotsy’s theory were considered from the basic pillars of his thinking which imply in the field of education, in order to understand how the individual develops from his/her experiential context.